2000
DOI: 10.1002/1099-0690(200009)2000:18<3223::aid-ejoc3223>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Cordiachromene

Abstract: An enantioselective synthesis of cordiachromene is described. An allylic alcohol moiety is first attached in the oposition to the methoxymethoxy substituent in 1-methoxy-4-methoxymethoxybenzene. Then chirality is introduced successively through asymmetric Sharpless epoxidation on the allylic alcohol moiety and regioselective ring-opening. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…24 The absolute configuration of the resulting 3a was assigned to be (R) by comparison of the sign of the specific rotation with the reported value. 15,16 This enantioselective 6-endo-trig cyclization of 1 seems to proceed through a general catalytic cycle of Wacker-type reaction, that is, an initial coordination of the olefin to Pd(II), a subsequent intramolecular attack of the nucleophile, and a final b-hydride elimination producing chromenes 3. From the results shown in Table 1, the use of ligand 4 is essential for promoting this cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…24 The absolute configuration of the resulting 3a was assigned to be (R) by comparison of the sign of the specific rotation with the reported value. 15,16 This enantioselective 6-endo-trig cyclization of 1 seems to proceed through a general catalytic cycle of Wacker-type reaction, that is, an initial coordination of the olefin to Pd(II), a subsequent intramolecular attack of the nucleophile, and a final b-hydride elimination producing chromenes 3. From the results shown in Table 1, the use of ligand 4 is essential for promoting this cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…In the last part of this study we report the application of the methodology shown above to the two‐step synthesis of deoxycordiachromene ( 4j ) 15. Thus, once the ring opening of 2,3‐benzofuran ( 1 ) took place as described above, the intermediate 2 was allowed to react with commercially available 6‐methyl‐5‐hepten‐2‐one under the same reaction conditions as for compounds 3 , giving the expected product 3j (45% isolated yield after column chromatography).…”
Section: Resultsmentioning
confidence: 99%
“…The residue was purified by column chromatography on a silica gel to give a MOM ether 1 . 1a , 9 1b , 10 1c , 11 1d , 12 1e , 13 1f , 14 1h , 15 and 4 (16) are known compounds.…”
Section: Methodsmentioning
confidence: 99%